Characterization of a large chromosomal "high-pathogenicity island" in biotype 1B Yersinia enterocolitica. - Carniel, E (1996)
Pathogenic Yersinia spp. can be subdivided into highly pathogenic (high-pathogenicity) and low-pathogenicity strains. Several genes specific for the high-pathogenicity strains are clustered on a chromosomal fragment designated a "high-pathogenicity island" (HPI). In the present work, the HPI of biotype 1B strain Ye 8081 of Y. enterocolitica was characterized. We demonstrate important differences from the HPI of Y. pestis. The HPI of Y. enterocolitica is smaller (45 kb) and is not flanked by insertion sequences. A copy of the gene coding for the tRNA-Asn is present at one extremity of the HPI and may, as in uropathogenic Escherichia coli, participate in the excision of the island. In addition to the genes encoding the yersiniabactin-pesticin receptor and the high-molecular-weight protein 2, four repeated sequences are present on the HPI of Y. enterocolitica. At least two of them are insertion elements: previously described IS1328 and newly characterized IS1400. Comparison of the HPI of strain Ye 8081 with that of other Y. enterocolitica strains of biotype 1B indicates that most of the island is conserved, apart from 15 kb at the left-hand end which is variable, especially in the region where three repeated sequences are clustered.